Systematic Placement of the Enigmatic Southeast Asian Genus Paralamium and an Updated Phylogeny of Tribe Pogostemoneae (Lamiaceae Subfamily Lamioideae) - Zhao, Fei; Wu, Yi-Wen; Drew, Bryan T.; Yao, Gang; Chen, Ya-Ping; Cai, Jie; Liu, En-De; Li, Bo; Xiang, Chun-Lei (Frontiers in Plant Science, 2021)
Paralamium (Lamiaceae) is a monotypic genus within the subfamily Lamioideae with a sporadic distribution in subtropical mountains of southeast Asia. Although recent studies have greatly improved our understanding of generic relationships within Lamioideae, the second most species-rich subfamily of Lamiaceae, the systematic position of Paralamium within the subfamily remains unclear. In this study, we investigate the phylogenetic placement of the genus using three datasets: (1) a 69,276 bp plastome alignment of Lamiaceae; (2) a five chloroplast DNA region dataset focusing on tribe Pogostemoneae, and (3) a nuclear ribosomal internal transcribed spacer region dataset of Pogostemoneae. These analyses demonstrate that Paralamium is a member of Pogostemoneae and sister to the monotypic genus Craniotome. In addition, generic-level phylogenetic relationships within Pogostemoneae are also discussed, and a dichotomous key for genera within Pogostemoneae is provided.